Comparison of Forward Chaining and Hill Climbing Methods in Blood Disease Diagnosis Expert Systems - Lydia Natalia Kristiani; Erdhi Widyarto Nugroho; Albertus Dwiyoga Widiantoro (Journal of Business and Technology, 2021)
Blood disease is a condition in which one or several parts of the blood can’t function normally. Blood disease itself is classified as quite mild but also some are classified as serious diseases and are usually genetic. Sometimes people underestimate the symptoms of mild illnes and lazy to see a doctor or laboratory because they think it troublesome and need to spend money. Therefore an early diagnosis of symptoms that may be related to blood disease is needed, so people can be alert and also prevent severe blodd disease. That’s why we need an expert system application that can help people diagnose and be aware of diseases that related to blood.